Assessing the Impact of Credit Risk Management on Profitability of Commercial Banks in Nepal - Amgain, Pushpa Nidhi; Sharma, Asmita Kumari; Manandar, Sures Kumar (Journal of Economics and Management, 2025)
This study aims to examine how the credit risk management influence on profitability of commercial banks in Nepal. The study was based on descriptive and causal comparative research design to address the issues of credit risk and performance of commercial banks. This study was based on secondary data and quantitate data in nature. There were 20 commercial banks operating in Nepal. So, all the commercial banks were used population for the study. Therefore, the sample size for this study were selected three commercial banks such as Nepal Bank Limited (NBL), Nabil Bank Limited (NABIL) and Kumari Bank Limited (KBL) as a sample bank from population using random sampling by lottery method. The secondary sources of data were collected from 2014/15 to 2023/24. The published financial statements of the sample commercial bank in Nepal as the recent fiscal year reported in the respective commercial bank’s website. This study was used descriptive analysis, correlation and multiple regression analysis during the study period using MS Excel 20 and SPSS version 26 software. The finding of the study revealed that NPLs illustrates that significant negative effect on return on assets (ROA). CAR showed a negative but statistically insignificant relationship with ROA. The credit to deposit ratio (CDR) was found a significant negative effect on ROA. The cash reserve ratio (CRR) demonstrated a positive but statistically insignificant relationship with ROA.NABIL bank demonstrated the sound financial performance and stability among the sampled commercial banks. The implication of the study emphasized the need for credit assessment procedures, continuous borrower monitoring and loan recovery mechanisms to control non- performing loans (NPLs). Future directions for research could be additional bank-specific factors such as bank size, leverage, cost to income ratio of development banks on profitability in Nepal.